HUBUNGAN KONTROL DIRI DENGAN PERILAKU CYBERSEX REMAJA PADA PENGGUNA WARUNG INTERNET DI GLAGAH SARI YOGYAKARTA - Ayu Indah Lestari; Hartosujono Hartosujono (Universitas Sarjanawiyata Tamansiswa, 2014)
ABSTRACT The purpose of this study is finding the relationship between self-control with teen cybersex behaviors on the user's internet cafe. The hypothesis of is there is a negative relationship between self-control with teen cybersex behaviors on the user's internet cafe. The subjects were users of internet cafes (cafe) in Glagah Sari Yogyakarta, aged 12-23 years, male sex and women, as well as the use of internet services in internet cafes (cafe), amounting to 80 people. Measuring instruments used are teen cybersex behavior scale and the scale of self-control. Analysis of data using techniques Karl Pearson Product Moment Correlation with the help of the statistical program SPSS version 20 for Mac. Based on the correlation of test results obtained by the correlation between the maturity value and the emotional tendencies cybersex behavior of - .229 with p = 0.005 (p<0.05). This suggests that the hypothesis that there is a negative relationship between self-control teen cybersex behavior is acceptable. This means that the higher the self-control the behavior of the lower cybersex. Conversely the lower the higher the self-control teen cybersex behavior.Key words: Cybersex, self-control, internet users